OP0317 ACCURACY OF THE OMERACT DEFINITIONS FOR IDENTIFICATION OF CALCIUM PYROPHOSPHATE CRYSTALS WITH ULTRASOUND: FINAL RESULTS OF THE OMERACT US IN CPPD SUB-TASK FORCE STUDY. (2nd June 2020) - Filippou, G.; Scanu, A.; Adinolfi, A.; Toscano, C.; Gambera, D.; Largo, R.; Naredo, E.; Calvo, E.; Herrero-Beaumont, G.; Zufferey, P.; Madelaine-Bonjour, C.; Maccarter, D.; et al.
Abstract : Background: The OMERACT Ultrasound (US) in calcium pyrophosphate deposition disease (CPPD) sub-task force has been working on the use of US in CPPD since 2014 first creating definitions for CPPD identification and then assessing the reliability[1]. Objectives: Objective of this study is to assess the diagnostic accuracy (truth) of US in CPPD. Methods: Consecutive patients waiting to undergo knee replacement surgery due to osteoarthritis were enrolled in 12 centres from 6 countries. Each patient underwent US examination of the knee, focusing on the menisci and the hyaline cartilage, the day prior to surgery, scoring each site for presence/absence of CPP as defined previously[1]. After surgery, the menisci and the condyles were retrieved and examined microscopically. Six samples were collected, both from the surface and from the internal part of menisci and cartilage trying to cover a large part of it. All slides were observed under transmitted light microscopy and by compensated polarised microscopy. A dichotomous score was given for the presence/absence of CPP. US and microscopic analysis were performed by different operators, blind to each other's findings. Sensitivity and specificity of US were calculated using microscopic findings as the gold standard. Results: 101 patients have been enrolled in the study. 33 patients have been excluded due to loss of anatomical pieces at surgery. The mean age of the remaining 68 pts was 71yo (±8), 44 women, 34 were affected by CPPD according to microscopy. Overall and per site diagnostic US accuracy results are presented in table 1 Conclusion: Our results demonstrate that US is an accurate exam for identification of CPPD. The best combination of sensitivity and specificity is achieved by examining the medial aspect of the knee. References: [1]Filippou G, Scirè CA, Adinolfi A, et al. Identification of calcium pyrophosphate deposition disease (CPPD) by ultrasound: reliability of the OMERACT definitions in an extended set of joints—an international multiobserver study by the OMERACT Calcium Pyrophosphate Deposition Disease Ultrasound Subtask Force. Ann Rheum Dis 2018;:annrheumdis-2017-212542. doi:10.1136/annrheumdis-2017-212542 Disclosure of Interests: Georgios Filippou: None declared, Anna Scanu: None declared, Antonella Adinolfi: None declared, Carmela Toscano: None declared, Dario Gambera: None declared, Raquel Largo: None declared, Esperanza Naredo: None declared, Emilio Calvo: None declared, Gabriel Herrero-Beaumont: None declared, Pascal Zufferey: None declared, Christel Madelaine-Bonjour: None declared, Daryl MacCarter: None declared, Stanley Makman: None declared, Zachary Weber: None declared, Fabiana Figus: None declared, Ingrid Möller: None declared, Marwin Gutierrez: None declared, Carlos Pineda: None declared, Denise Clavijo Cornejo: None declared, Héctor García: None declared, Victor Ilizaliturri: None declared, Jaime Mendoza Torres: None declared, Raul Pichardo: None declared, Luis Carlos Rodriguez Delgado: None declared, Emilio Filippucci Speakers bureau: Dr. Filippucci reports personal fees from AbbVie, personal fees from Bristol-Myers Squibb, personal fees from Celgene, personal fees from Roche, personal fees from Union Chimique Belge Pharma, personal fees from Pfizer, outside the submitted work., Edoardo Cipolletta: None declared, Teodora Serban: None declared, Catalin Cirstoiu: None declared, Florentin Ananu Vreju: None declared, Dun Grecu: None declared, Gael Mouterde: None declared, Marcello Govoni: None declared, Leonardo Punzi: None declared, Nemanja Damjanov Grant/research support from: from AbbVie, Pfizer, and Roche, Consultant of: AbbVie, Gedeon Richter, Merck, Novartis, Pfizer, and Roche, Speakers bureau: AbbVie, Gedeon Richter, Merck, Novartis, Pfizer, and Roche, Lene Terslev Speakers bureau: LT declares speakers fees from Roche, MSD, BMS, Pfizer, AbbVie, Novartis, and Janssen., Carlo Alberto Scirè: None declared, Annamaria Iagnocco Grant/research support from: Abbvie, MSD and Alfasigma, Consultant of: AbbVie, Abiogen, Alfasigma, Biogen, BMS, Celgene, Eli-Lilly, Janssen, MSD, Novartis, Sanofi and Sanofi Genzyme, Speakers bureau: AbbVie, Alfasigma, BMS, Eli-Lilly, Janssen, MSD, Novartis, Sanofi